Real Earnings Management as a Tool for Big Bath Creating in Industrial Companies - Comporek, Michał (Journal of Finance and Financial Law, 2021)
The purpose of the article/hypothesis: The aim of the paper is to show the importance of the implemented real earnings management (REM) in the intentional shaping of large losses in public industrial enterprises listed on the Warsaw Stock Exchange. Methodology: The basic method of assessing the REM activities was compliant with the Roychowdhury methodology, enabling the estimation of the abnormal levels of: operational cash flows, production costs and discretionary expenses. In turn, the modified verision of iosik model was used to assess the impact of REM practices on the frequency of large losses in tested sample. Results of the research: The obtained results show that the REM implemented by means of overproduction, granting above-average rebates and a liberal approach in the field of trade credits may be considered an important path of intentional deepening of the net loss in public industrial companies.